Artificial intelligence-based chatbots – a motivation underlying sustainable development in banking: standpoint of customer experience and behavioral outcomes - Tran Hung Nguyen; Xuan Cu Le (Cogent Business & Management)
In the digital transformation scenario, banks must strengthen business sustainability through digital technologies, such as artificial intelligence-based chatbots. Crucial evidence illustrates that using chatbots allows banks to enhance business performance and bank–customer relationship. This study aims to unveil how chatbots bring customer experiences and whether customers adopt behavioral outcomes. Structural equation modeling is calculated to examine the hypotheses of a postulated research model with a valid sample of 336 respondents. The results reveal that extrinsic value is investigated because of the central indispensability of chatbot attributes, including understandability, automation, and competence. Meanwhile, understandability, personalization, interaction, and intimacy are of paramount importance in increasing the intrinsic value toward chatbot usage. Intrusiveness tends to inhibit customers’ intrinsic value. Furthermore, extrinsic and intrinsic values significantly predict customer satisfaction and continuance intention toward banking chatbots. Additionally, satisfaction is a motivation for customer intention to sustain the use of banking chatbots. In light of the obtained findings, it is imperative for banks to deem chatbot characteristics as the determinative motivations for customer experience because chatbots provide customers with valuable information and have the capability to address financial issues.